Peran Pojok Baca dalam Menumbuhkan Literasi Anak Usia Dini di TK/PAUD Khairul Shidiq - Mufidatun Nashiroh; Annisa Sri Restanti (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Literacy is a very crucial skill that must be developed from an early age because it serves as the foundation for the lifelong learning process. One effective way to increase children’s interest in reading is by providing a reading corner that is both child-friendly and easily accessible. This study aims to explore the role of the reading corner in enhancing children’s literacy at Khairul Shidiq Kindergarten/PAUD. The research method used is qualitative descriptive with data collection techniques that include observation, interviews, literature review, and documentation. The findings of this study indicate that the reading corner at Khairul Shidiq Kindergarten/PAUD has been actively utilized in various literacy activities. These activities include structured reading programs with prizes, awards for children who consistently show enthusiasm in reading, storytelling sessions, and singing together, all of which contribute to creating a joyful learning environment. Despite these positive efforts, several challenges remain in the management of the reading corner, such as the limited number of book collections, the lack of variation in reading materials, and the absence of a dedicated librarian who can organize and develop literacy activities more systematically. Nevertheless, the reading corner has proven to play a significant role in fostering children’s interest in reading and in strengthening their early literacy skills. Therefore, it can be concluded that the reading corner is an effective method for cultivating a literacy culture in early childhood education settings, particularly in pre-school institutions.